Contact with mental health services in the 12-month period before offending in a cohort of forensic order patients. Issue 6 (2nd November 2021) - Green, Bob; Steele, Megan L.; Davidson, Fiona; Neillie, Darren
Abstract : There has been limited research examining the details of mental health service contact in the pre-offending period. A retrospective case-note study of the complete cohort of people found not criminally responsible or permanently unfit for trial in Queensland, Australia, was conducted. An electronic clinical database search for seven treatment event types in the 12-months pre-offence was conducted. Of the 123 eligible patients, half were recorded as having experienced at least one treatment event. There was a statistically significant increase in the number of patients experiencing a treatment-related event per month over this 12-month pre-offence period (increase of ∼1.4 patients per month, p < .001). The findings highlight the need for appropriate weight to be placed on both longitudinal and recent factors when undertaking routine clinical review or mental health assessment, or considering changes to a patient's diagnosis and treatment plan. Screening in custody and early intervention are also indicated to ensure appropriate treatment.